#TITLE_ALTERNATIVE# - PAMBAYUN SEKAR KINANTHI (NIM : 10309025); Pembimbing : Dr. Dhani Herdiwijaya, M.Sc , RETYANTI
Solar activity causes changes in the Earth's magnetic field. One manifestation of this change can be seen from the emergence of Aurora that has a changing pattern and shape. Based on POES Satellites, Aurora's emergence variability of the amount of power can be classified in units of gigawatts. This quantity represents the flux of electrons in the polar regions. Aurora's brightness is proportional to the flux of electrons. Writer is looking for a correlation between the power with solar activity and other geomagnetic indices that occur on Earth in the period 1999-2009 with a resolution of one hour. The parameters used are: solar parameters (speed plasma, proton density, flares and CME) and the geomagnetic parameters (magnetic field, Dst index, and AE index). The biggest correlation coefficient occurred are proton density and magnetic field direction z, although this value is too small at less than 10%. The results are then analyzed further by analyzing the parameters of the Sun and geomagnetic since five days before the highest Aurora power. Based on data from flares and CME, Aurora high power associated with high-energy flares (classes M and X) and the halo-type of CME. The phenomenon can cause a shockwave for speed and density of the solar wind protons, so Aurora can be preceded by a high-power arrival of shockwave. Additionally, flare and CME causes a strong increase in interplanetary magnetic field component, especially for Bz. These shockwaves and an increase in Bz component can trigger an intensification of geomagnetic indices Dst and AE.